Contribution to the knowlegde of Galician xenoflora, II (NW Iberian Peninsula, Spain). - González-Martínez, X. Ignacio (Botanica Complutensis, 2017)
In the present study, we present information about 25 exotic plants collected in different environments at SW of the province of A Coruña. The total includes 7 first records at a regional level [Actinidia chinensis Planch., Fatsia japonica Planch., Fuchsia magellanica Lam., Fuchsia × hybrida Hort. ex Sieber & Voss, Kalanchoe × houghtonii D.B.Ward, Kerria japonica (L.) DC. and Ligustrum lucidum W.T. Aiton], and 6 provincial novelties [Achyrocline satureioides (Lam.) DC., Ageratina adenophora (Spreng.) R.M. King & H. Rob., Chlorophytum comosum (Thunb.) Jacq., Eucalyptus pulchella Desf., Impatiens balfourii Hook. fil. and Muehlenbeckia complexa (A. Cunn.) Meisn.]. In addition, information about several taxa hardly mentioned in Galicia or with some taxonomic problem is also included. On the other hand, we have decided include the horticultural hybrid Leucanthemum × superbum (Bergmans ex J.W. Ingram) D.H. Kent, novelty for the Iberian flora. All specimens are deposited in the SANT Herbarium.
Keywords: Vascular plants; alien taxa; chorology; taxonomy; ecology; A Coruña.